2023
DOI: 10.1101/2023.04.20.537671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collagen and actin network mediate antiviral immunity against Orsay in C. elegans intestinal cells

Abstract: C. elegans is a free-living nematode that is widely used as a small animal model for studying fundamental biological processes and disease mechanisms. Since the discovery of the Orsay virus in 2011, C. elegans also holds the promise of dissecting virus-host interaction networks and innate antiviral immunity pathways in an intact animal. Orsay primarily targets the worm intestine, causing enlarged intestinal lumen as well as visible changes to infected cells such as liquefaction of cytoplasm and rearrangement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We also observed that the relative infected area per worm did not increase over time, which may be due to the differential localization of anti-viral genes within the intestine. It has been recently reported that intestinal cross-linking collagens, which are restricted to the posterior intestinal cells, mediate antiviral immunity in the intestine (Zhou et al, 2023), with intestinal RNAi of different collagens resulting in increased viral loads. This increase in viral load may thus be due to an increased number of infected cells, as we observed in the lys-2 and drh-1 mutants.…”
Section: Orv Dynamics Along Larval Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that the relative infected area per worm did not increase over time, which may be due to the differential localization of anti-viral genes within the intestine. It has been recently reported that intestinal cross-linking collagens, which are restricted to the posterior intestinal cells, mediate antiviral immunity in the intestine (Zhou et al, 2023), with intestinal RNAi of different collagens resulting in increased viral loads. This increase in viral load may thus be due to an increased number of infected cells, as we observed in the lys-2 and drh-1 mutants.…”
Section: Orv Dynamics Along Larval Developmentmentioning
confidence: 99%
“…Several conserved antiviral defense mechanisms that C. elegans uses against OrV infection have been described, including (i) the RNA interference pathway, which degrades viral RNA and triggers antiviral gene expression (Ashe et al, 2013;Chen et al, 2017;Sowa et al, 2020); (ii) viral RNA uridylation, which targets viral RNA to degradation (Le Pen et al, 2018); and (iii) expression of antiviral genes, which include protein ubiquitination for targeted degradation and the activation of the intracellular pathogen response (IPR), which is a common response to intracellular pathogens and stresses (Bakowski et al, 2014;Chen et al, 2017;Reddy et al, 2017Reddy et al, , 2019). In addition, several studies have described pathways necessary for OrV replication, such as zinc and the lipid metabolism (Casorla-Perez et al, 2022a), chromatin remodeling and cytoskeleton rearrangements (Zhou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Follow‐up studies have demonstrated that these proteins share conserved function with their mammalian homologs (Jiang et al., 2019, 2020). Recent studies have also implicated a role for structural proteins (i.e., actin, collagen) and the endoplasmic reticulum in mediating antiviral defense (Efstathiou et al., 2022; Zhou et al., 2024). Curiously, several of the collagen components identified as antiviral factors in C. elegans are homologs of human proteins involved in innate immune responses (Zhou et al., 2024).…”
Section: Commentarymentioning
confidence: 99%
“…Recent studies have also implicated a role for structural proteins (i.e., actin, collagen) and the endoplasmic reticulum in mediating antiviral defense (Efstathiou et al., 2022; Zhou et al., 2024). Curiously, several of the collagen components identified as antiviral factors in C. elegans are homologs of human proteins involved in innate immune responses (Zhou et al., 2024). These findings lend support to the potential of the C. elegans ‐virus model for discovering novel antiviral factors that are conserved in mammals.…”
Section: Commentarymentioning
confidence: 99%